Answer:(X+3)(X+6)
Step-by-step explanation:
(a+b+c)^3=a^3 +b^3+c^3-2(ab+ac+bc)
216=a^3+b^3+c^3-2(11)
a^3+b^3+c^3=238
but ıdk how can ı find -3abc :/
===============================================
Work Shown:
a+b+c = 6
(a+b+c)^2 = 6^2
(a+b+c)(a+b+c) = 36
a(a+b+c)+b(a+b+c)+c(a+b+c) = 36
a^2+ab+ca+ab+b^2+ca+bc+c^2 = 36
a^2+b^2+c^2+2ab+2bc+2ca = 36
a^2+b^2+c^2+2(ab+bc+ca) = 36
a^2+b^2+c^2+2*11 = 36
a^2+b^2+c^2+22 = 36
a^2+b^2+c^2 = 36-22
a^2+b^2+c^2 = 14
-----------------------
a^3+b^3+c^3-3abc = (a+b+c)*(a^2+b^2+c^2 - (ab+bc+ca) )
a^3+b^3+c^3-3abc = 6*(14 - 11)
a^3+b^3+c^3-3abc = 18
Answer:
c = 30°
d = 60°
Step-by-step explanation:
Angle ZWC is a 90° angle
Angle YWX is a 60° angle
add them together and you get 150°
180 - 150 = c = 30°
c + d + 90° = 180°
substitute
30° + d + 90° = 180°
combine like terms
120° + d = 180°
subtract 120° from both sides
d = 60°
hope this helps!!
Answer:
c is 30 and d is 60
Step-by-step explanation:
I did it for hw
2x+y=82x+y=8
If we double each side of the second equation, 2x+y=82x+y=8, we have 4x+2y=164x+2y=16. Explain why the same pair that is the solution to the system is also a solution to this new equation.
If needed, you can support your explanation with hanger diagrams (upload a picture), or by inventing a situation that the equations represent.
If we add the two equations in the original system, we have 6x+7y=326x+7y=32. Explain why the same (x, y) pair is also a solution to this equation.
Again, you can support your explanation with diagrams or a situation, if needed.
The equations are a system of linear equations. Modifying them through multiplication or addition while keeping both sides balanced doesn't change the solution. Any pair (x,y) satisfying one equation will satisfy the others.
In mathematics, these equations are a system of linear equations. This is essentially a set of two or more equations, with a common set of variables. The same pair (x, y) are the solutions for all equations, as the second equation is a simplified, scalar multiple of the first.
So, for the first original equation (4x + 6y = 24), and the modified one (4x + 2y=16) which is the second equation of the system doubled, we can see that the multiplier is the same for both the 'x' and 'y' on the left side, and the right side of the equation. Therefore, if a pair (x,y) has been found to satisfy the first equation, it will also work for the second, as essentially, the equations are equivalent.
Similarly, adding the original system of equations, we get 6x + 7y = 32. This also has the same solution set, just expressed differently. As long as you're performing the same operation (like doubling, adding etc.) to each side of the equations, the balance remains constant, retaining the same solution.
#SPJ12
Answer:
7.9
Step-by-step explanation:
because you don't make sentence